Pengaruh Model Pembelajaran Discovery Learning Terhadap Keterampilan Berpikir Kritis Siswa Pada Materi Sistem Ekskresi - Marjan, Eyovin Payunang; Fatmawati, Any; Harisanti, Baiq Muli (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Discovery Learning is a fairly effective learning model as an effort to gain knowledge and will be remembered for a long time because this method provides an opportunity for students to develop ways of thinking and explore the relationships between lesson concepts. Critical thinking skills allow students to develop analytical and evaluative abilities, so that students can understand the situation as a whole and make the right decisions. This study aims to determine the effect of the Discovery Learning learning model on the critical thinking skills of high school students on the excretory system material. This research was conducted in the 11th grade students of SMA Negeri 1 Pringgasela, East Lombok, West Nusa Tenggara in the even semester of the 2023/2024 academic year with 54 students as research subjects. This type of research is a quasi-experiment. The experimental class uses the Discovery Learning learning model, namely class XI-F3, while the control class uses the conventional learning model, namely class XI-F6. The instrument used is a descriptive test of 6 questions. After the pre-test and post-test data were obtained, the data obtained were analyzed using SPSS. Based on the hypothesis test, the Sig. value was obtained. (2-tailed) which is 0.050 â‰¤ 0.05 means that there is an influence of the Discovery Learning learning model on students’ critical thinking skills.